Fatherlessness as an Urban Social Phenomenon: A Study of the Absence of Fathers' Roles in Families in Bandung City, Indonesia - Irwandi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Fatherlessness has become an increasingly important social issue in urban communities, characterized not only by the physical absence of fathers but also by their limited emotional, educational, and social involvement in family life. This study aims to examine fatherlessness as an urban social phenomenon in Bandung City by identifying its forms, exploring the social factors contributing to fathers' absence, and analyzing its implications for family resilience. A qualitative case study approach was employed through in-depth interviews, observations, and document analysis involving fathers, mothers, adolescents, psychologists, social workers, and government representatives. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings are expected to show that fatherlessness is shaped by interconnected factors, including economic pressures, demanding work patterns, family instability, urban lifestyles, and changing gender roles, which collectively reduce fathers' involvement in parenting despite their physical presence. The study proposes an Urban Fatherlessness Model that explains fatherlessness as a consequence of urban social transformation and highlights the importance of strengthening paternal engagement through family-based interventions, community support, and responsive public policies. By positioning fatherlessness within the context of urban sociology rather than solely child psychology, this study contributes to a broader understanding of family change and provides insights for policies aimed at enhancing family resilience in urban settings.